Fourteen new Polynucleobacter species: P. brandtiae sp. nov., P. kasalickyi sp. nov., P. antarcticus sp. nov., P. arcticus sp. nov., P. tropicus sp. nov., P. bastaniensis sp. nov., P. corsicus sp. nov., P. finlandensis sp. nov., P. ibericus sp. nov., P. hallstattensis sp. nov., P. alcilacus sp. nov., P. nymphae sp. nov., P. paludilacus sp. nov. and P. parvulilacunae sp. nov. Issue 6 (13th June 2022) - Hahn, Martin W.; Pitt, Alexandra; Schmidt, Johanna; Camacho, Antonio
Abstract : Fourteen strains, all isolated from the surface of freshwater habitats, were genomically, phylogenetically and phenotypically characterized. The strains were obtained from geographically and climatically broadly scattered sites. This included two lakes in Antarctica, one arctic pond located on the Svalbard archipelago (Norway), a tropical habitat located in Uganda, some lakes in Southern Europe (Spain and France), lakes, ponds and a puddle in Central Europe (Austria, Czech Republic and Germany), and lakes in Northern Europe (Finland). Most of the investigated strains were characterized by rather small cell sizes and rather slow growth on media such as nutrient broth–soyotone–yeast extract (NSY) medium. Phylogenomic analyses indicated that all fourteen strains are affiliated with the genus Polynucleobacter ( Burkholderiaceae, Pseudomonadota ). Thirteen of the strains were found to be affiliated with subcluster PnecC of the genus. All these strains were characterized by genome sizes in the range of 1.7–2.3 Mbp and G+C values of 44.9–46.5 mol%. Furthermore, all PnecC-affiliated strains shared 16S rRNA gene sequence similarities >99 %. Only one strain characterized by a larger genome size of 2.9 Mbp and a lower G+C value of 41.0 mol% was found to be affiliated with subcluster PnecA. Whole genome sequence comparisons revealed that all 14 strains shared among each other, as well as with the type strains of the previously described 17 Polynucleobacter species, whole-genome average nucleotide identities values <95 %. This suggested that the 14 investigated strains represent 14 different new species. We propose the establishment of 14 new Polynucleobacter species represented by the following type strains: UB-Domo-W1 T (=DSM 103491 T =CIP 111598 T =JCM 32562 T ), VK13 T (=DSM 103488 T =JCM 32564 T ), LimPoW16 T (=DSM 24085 T =CIP 111098 T ), UK-Long2-W17 T (=DSM 103489 T =CIP 111328 T =JCM 32563 T ), UK-Pondora-W15 T (=DSM 103423 T =JCM 32939 T ), MWH-Mekk-B1 T (=DSM 106779 T =JCM 32556 T ), MWH-Mekk-C3 T (=DSM 103415 T =JCM 32557 T ), Ross1-W9 T (=DSM 103416 T =JCM 32561 T ), MWH-Hall10 T (=DSM 107042 T =JCM 32938 T ), AP-Basta-1000A-D1 T (=DSM 107039 T =JCM 32933 T ), AP-Melu-1000-A1 T (=DSM 107036 T =JCM 32935 T ), es-MAR-2 T (=DSM 103424 T =JCM 32554 T ), AP-Mumm-500A-B3 T (=DSM 107037 T =JCM 32936 T ), MWH-UH21B T (=DSM 23884 T =LMG 29707 T ).